Prevalence of Helicobacter pylori infection among blood donors in Saxony-Anhalt, Germany – a region at intermediate risk for gastric cancer - Franck, Caspar; Hoffmann, Armin; Link, Alexander; Schulz, Christian; Wuttig, Kerstin; Becker, Elke; Heim, Marcell; Venerito, Marino; Malfertheiner, Peter (Zeitschrift für Gastroenterologie, 2017)
Background In the federal state of Saxony-Anhalt, gastric cancer (GC) incidence ranks among the highest in Germany. Helicobacter pylori prevalence is a surrogate marker for GC risk in a given population. In 2010 we reported an H. pylori seroprevalence of 44.4 % in patients at the emergency ward of the University Hospital of Magdeburg, the capital of Saxony-Anhalt. Our aim is to update these findings in a cohort of healthy blood donors from the same region.Materials and methods The sera of 516 consecutive blood donors (40.1 ± 14.1 years; 286 males and 230 females) were tested for antibodies against H. pylori and CagA. Data on demographics and previous H. pylori eradication therapy were obtained by means of a structured questionnaire. Blood donors with positive serology for H. pylori or CagA and/or history of eradication therapy were classified as H. pylori-positive.Results Overall, 28.9 % of the study cohort were H. pylori-positive. The prevalence was higher in older generations (9 % in 18 – 20 years up to 47 % in 61 – 70 years). In 44.4 % of H. pylori IgG-positive donors, CagA serology was also positive. This proportion was not age-dependent. Study participants with siblings were by trend more often H. pylori-positive (p = 0.066).Conclusion Compared to our previous study in patients at the emergency ward, we found by trend lower age-related H. pylori prevalence rates. In our cohort of healthy blood donors, we confirmed a lower H. pylori prevalence in younger generations.
Keywords: cagA; eradication therapy; gastric cancer; Germany; helicobacter pylori; infection; prevalence; Saxony-Anhalt; serological test; seroprevalence